Thalidomide in the treatment of cancer cachexia: a randomised placebo controlled trial. Issue 4 (7th March 2005) - Gordon, J N; Trebble, T M; Ellis, R D; Duncan, H D; Johns, T; Goggin, P M
Abstract : Background: Proinflammatory cytokines, especially tumour necrosis factor α (TNF-α), play a prominent role in the pathogenesis of cancer cachexia. Thalidomide, which is an inhibitor of TNF-α synthesis, may represent a novel and rational approach to the treatment of cancer cachexia. Aims: To assess the safety and efficacy of thalidomide in attenuating weight loss in patients with cachexia secondary to advanced pancreatic cancer. Methods: Fifty patients with advanced pancreatic cancer who had lost at least 10% of their body weight were randomised to receive thalidomide 200 mg daily or placebo for 24 weeks in a single centre, double blind, randomised controlled trial. The primary outcome was change in weight and nutritional status. Results: Thirty three patients (16 control, 17 thalidomide) were evaluated at four weeks, and 20 patients (eight control, 12 thalidomide) at eight weeks. At four weeks, patients who received thalidomide had gained on average 0.37 kg in weight and 1.0 cm 3 in arm muscle mass (AMA) compared with a loss of 2.21 kg (absolute difference −2.59 kg (95% confidence interval (CI) −4.3 to −0.8); p = 0.005) and 4.46 cm 3 (absolute difference −5.6 cm 3 (95% CI −8.9 to −2.2); p = 0.002) in the placebo group. At eight weeks, patients in the thalidomide group had lost 0.06 kg in weight and 0.5 cm 3 in AMA compared with a loss of 3.62 kg (absolute difference −3.57 kg (95% CI −6.8 to −0.3); p = 0.034) and 8.4 cm 3 (absolute difference −7.9 cm 3 (95% CI −14.0 to −1.8); p = 0.014) in the placebo group. Improvement in physical functioning correlated positively with weight gain ( r  = 0.56, p = 0.001). Conclusion: Thalidomide was well tolerated and effective at attenuating loss of weight and lean body mass in patients with cachexia due to advanced pancreatic cancer.